Pengaruh Kepemimpinan Transformasional,Keadilan Organisasional, Kepercayaan Organisasional, Kepuasan Kerja terhadap Organizational Citizenship Behavior (Studi pada Perguruan Tinggi Swasta di Kalimantan Timur) - Sabran -; Armanu Thoyib; Eka Afnan Troena; Ubud Salim (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
Internally, in order to realize organizational citizenship behavior, we need strong leadership, in this case, the transformational leadership which is capable to bring changes to the university itself. This study was aimed to knowed influence of the transformational leadership, organizational justice, organizational trust and job satisfaction towards the organizational citizenship bevior of the lectures at the private universities in East Kalimantan. The Sampling technique used was multistage sampling, i.e. a step by step sampling method by taking 10% of the number of sample because it amounted to more 100. The number of sample in this research was 140. The research findings showed that: First: Ttransformational leadership had a significant influence toward organizational justice, Second: Transformational leadership had significant influence toward organizational trust, Third: Organizational justice had significant influence toward organizational trust, Fourth: transformational leadership did not have influence toward job satisfaction, Fifth: organizational justice significantly influenced job satisfaction, Sixth: Organizational trust significantly influenced on job satisfaction, Seventh: Transformational leadership significantly influenced organizational citizenship behavior Eighth: Organizational justice significantly influenced organizational citizenship behavior, Ninth: Organizational trust significantly influenced organizational citizenship behavior, Tenth: Job satisfaction significantly influenced organizational citizenship behavior.Keywords: Transformational Leadership, Organizational Justice, Organizational Trust, Job Satisfaction, organizational citizenship behavior.